Regulation of neutrophil extracellular trap formation by c-di-GMP in Pseudomonas aeruginosa-induced pleural infection - Qing, Cao; Huang, WenHui; Shi, Lilu; Luo, Jing; Zheng, Shaochu; Kong, Jinliang; Wang, Ke (Frontiers in Immunology, 2025)
BackgroundPseudomonas aeruginosa(P.aeruginosa)employs c-di-GMP to govern biofilm formation and virulence, enhancing bacterial adhesion and immune evasion. In pleural infections, c-di-GMP simultaneously promotes invasion and modulates neutrophil extracellular traps (NETs), though its mechanistic role remains undefined. While c-di-GMP’s pathogenic contributions are established, its specific regulation of NETs formation during pleural infection has not been explored. Our study investigates c-di-GMP-driven NETs generation in murine infection models.MethodC57BL/6J mice were infected with P.aeruginosa strains expressing high (PAO1△wspF), wild-type (PAO1), or low (PAO1/plac-yhjH) c-di-GMP levels to establish pleural infection. In vitro, c-di-GMP levels and biofilm formation of strains were verified using pcdrA-gfp reporter, crystal violet staining, and confocal microscopy. In vivo, pleural histopathology was observed via HE staining, confocal microscopy and scanning electron microscopy (SEM); RNA sequencing (RNA-seq) of mouse pleural lavage fluid cells was performed, followed by Mfuzz clustering, KEGG/GO enrichment analysis, and protein-protein interaction (PPI) network construction to identify key regulatory genes. Candidate genes (e.g., Cybb, Mapk14, Pik3cd) were validated by qRT-PCR. NETs formation was quantified via immunofluorescence, and measurements of cell-free DNA (cf-DNA) and myeloperoxidase-DNA (MPO-DNA) complexes in pleural lavage fluid.ResultIn vitro, PAO1△wspF showed the highest c-di-GMP level and biofilm formation, followed by PAO1 and PAO1/plac-yhjH. In vivo, infected mice exhibited thoracic purulent secretions and parietal pleura thickening (vs. PBS control), with no obvious morphological differences among the three infected groups. RNA-seq and Mfuzz clustering identified 5 continuously downregulated gene clusters in infected mice; KEGG enrichment showed 48 genes enriched in the ‘neutrophil extracellular trap formation’ pathway. PPI network analysis screened 10 hub genes (including Cybb, Mapk14, Pik3cd), whose differential expression was confirmed by qRT-PCR (p<0.05). NETs detection revealed a c-di-GMP-dependent trend: PAO1△wspF induced the strongest NETs response (highest immunofluorescence intensity, cf-DNA, and MPO-DNA levels), followed by PAO1 and PAO1/plac-yhjH.ConclusionsThis work reveals how P.aeruginosa’s c-di-GMP controls NETs formation in murine pleural infections, bridging bacterial virulence mechanisms with host immune responses. By identifying key regulatory genes, it establishes groundwork for targeted anti-biofilm therapies against chronic infections.